Propriété foncière et propriété du capital en AlgérieLe foncier agricole, de l’autogestion à la concession - Ammar Belhimer (L’Année du Maghreb)
Ignored for long, private property was eventually consecrated by the financial constraints induced by the 1996 oil crisis. The state disengagement from the economic sphere led to a more and more accepted privatization, which became constitutionalized in Article 37 of the 1996 fundamental law regarding the freedom of trade and industry. But this process did not reflect an internal, socio-economic maturity but external injunctions which became more pressing after the agreement passed with IMF in May 1994. However, the privatization device undertaken under the periodic performance control by IMF experts remains heavily affected by administrative and bureaucratic obstacles since the role of the state, as the rent distributor and the private accumulation supervisor (in the land, commercial and industrial domains), keeps on being essential. If this scheme comes to its logical end, it might be said that no bourgeoisie was ever so organically linked to a state paradoxically voluntarist and anti-capitalist.